From awareness to cultural agency: efl colombian student teachers’ travelling abroad experiences (2015)
Colombian English as a foreign language student teachers’ opportunities to grow as educators through international sojourns do not usually subsume the traditional study and residence abroad goal. This was the case for our participants who engaged mainly in working abroad with study being ancillary. Fifty student teachers from two public universities reported how their international sojourn bolstered their intercultural learning. Three different programs, disconnected from participants’ academic institutions, became vehicles for their experiences abroad. Surveys and interviews reveal that participants’ origin, selected programs, and contextual circumstances influenced their intercultural learning. As a result, intercultural development gravitated towards awareness of intercultural patterns, critical reading of culture, and pre-service teachers’ repositioning to build cultural agency. Implications suggest the need to connect traveling abroad programs to undergraduate curricula.Las oportunidades de crecimiento que futuros docentes colombianos de inglés obtienen al participar en programas para viajar al exterior, usualmente no reflejan las metas en el área de residencia y estudios en el extranjero. Un porcentaje alto de los participantes reportaron experiencias de trabajo, relegando sus objetivos académicos a un segundo plano. Cincuenta estudiantes de dos universidades públicas, quienes viajaron con tres programas no conectados oficialmente con sus universidades, reportan cómo su experiencia fortaleció su aprendizaje intercultural. Encuestas y entrevistas develaron el origen y perfil de los participantes, los programas seleccionados y circunstancias contextuales como factores en su aprendizaje. Además, los participantes identificaron patrones interculturales, lograron una lectura crítica de la cultura y un reposicionamiento en la construcción de agencia cultural. Las implicaciones discuten la necesidad de conectar estos programas de viaje con los currículos de pregrado.